(untitled) (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2022)
This study aims to produce modules and describe validation and describe the effectiveness of story-based braille module designs with a humanistic approach to improve the values of independence of ABK students. This study used the R&D method. The subject of the study was a middle-level or grade IX Donbosco SLB student. The steps used in this study are data collection, product design/model I, expert validation/model II, product revision, and product implementation. Based on the results of expert validation obtained by 87%, learning media have expert reviews of 92%. It has shown a very valid category, and the story-based braille module has been declared viable and usable. We filled out a questionnaire and gave it to our students, achieving a percentage of 90% It shows that the design of story-based braille modules with a humanistic approach to improving the values of independence of ABK students is effectively used in learning with an "excellent" level of effectiveness.